(untitled) (Journal of Applied Oral Science, 2017)
Dental applications based on the unique characteristics of amorphous calcium phosphate stabilized by casein phosphopeptides (CPP-ACP) have been proposed, as well as the improvement of its properties. Objectives: The objective of this study was to determine the ability of topically applied CPP-ACP from a commercial product to remineralize subsurface lesions when applied for extended periods of time (3 h and 8 h). Material and Methods: Artificially induced carious lesions were produced in 50 bovine enamel blocks previously selected by surface hardness. After treatments with gel without F and CPP-ACP applied for 1 minute (Placebo); 2% NaF neutral gel applied for 1 minute (Fluoride 1 min); CPP-ACP applied for 3 min (ACP 3 min); and CPP-ACP applied for 3 h (ACP 3 h) and for 8 h (ACP 8 h), the enamel blocks were submitted to the remineralization pH-cycling. Surface hardness and synchrotron micro-tomography were used to determine the percentage of surface hardness recovery (%SHR) and to calculate mineral concentration (gHAp.cm−3), respectively. The data were submitted to ANOVA followed by the Student-Newman-Keuls test (p